ANALISIS PENGARUH INDEPENDENSI AUDITOR, KARAKTERISTIK PERUSAHAAN, KUALITAS AUDITOR DAN PERGANTIAN AUDITOR TERHADAP INTEGRITAS LAPORAN KEUANGAN - Irfan Auditya; Provita Wijayanti (Jurnal Akuntansi Indonesia, 2013)
This study aimed to analyze the influence of auditor independence, corporate characteristics, quality auditors and auditor turnover for the integrity of the financial statements. The study population is a company listed on the Indonesia Stock Exchange from 2008 until 2010. The sample selection based on purposive sampling method and obtained a sample of 38 companies. Then analyzed with multiple regression. The results showed that the change of ownership of managers and auditors significantly affect the integrity of the financial statements. While the auditor independence variables, firm characteristics, quality auditor is not significant